Web-Based Product Marketing Information System Design at Definier Store - Euis Nurninawati; M. Yusuf Effendy; Andhika Maulana Rianputra (International Institute for Advanced Science & Technology (IIAST), 2023)
Definier is a product brand that is engaged in accessories. The development of this store is quite fast because in 2020 there have been many orders from outside the city/district. This is because many customers spread information about the existence of this store and the quality of the goods sold. The research supported by this paper aims to help Definier have or have an overview of a Website that will support promotion and marketing in the world of the digital era. The problems faced According to this definition, a better marketing system is needed so that enthusiasts who come from outside the city can purchase goods without difficulty due to long distances. Therefore, the researcher created a web-based product marketing information system that serves to help store marketing become wider. The analytical method used is the pieces method by obtaining more specific issues in making this product marketing information system customers from outside the city. helped to make purchase transactions, where all information about the store is the address, contact of the store, and a list of goods sold along with pictures of the goods. This website is made using the windows operating system using the php web hosting platform and using the mysql database. The conclusion of this research is the implementation of a Web-Based Marketing Information System at the Definier store, which is to facilitate wider product marketing, with a modern appearance and a good user interface and easy to use by the public. this Definier store will be even better in the future and also help facilitate the marketing of the Definier store.